In-hospital outcomes in invasively managed acute myocardial infarction patients who receive morphine - McCarthy, Cian P; Bhambhani, Vijeta; Pomerantsev, Eugene; Wasfy, Jason H (Journal of interventional cardiology, 2018)
We aimed to analyze the association between morphine and in-hospital outcomes in invasively managed ST elevation myocardial infarction (STEMI) and non-ST elevation acute coronary syndrome (NSTE-ACS) patients. Morphine is commonly used for analgesia in the setting of acute coronary syndromes (ACS); however, recently its utility in ACS has come under closer scrutiny. We identified all STEMI and NSTE-ACS patients undergoing coronary angiogram +/- percutaneous intervention between January 2009 and July 2016 in our center and recorded patient characteristics and inpatient outcomes. Overall, 3027 patients were examined. Overall, STEMI patients who received morphine had no difference in in-hospital mortality [4.18% vs. 7.54%, odds ratio (OR): 0.36, P = 0.19], infarct size (mean troponin level 0.75 ng/mL vs. 1.29 ng/mL, P = 0.32) or length of hospital stay (P = 0.61). The NSTE-ACS patients who received morphine had a longer hospital stay (mean 6.58 days vs. 4.78 days, P < 0.0001) and larger infarct size (mean troponin 1.16 ng/mL vs. 0.90 ng/mL, P = 0.02). Comparing matched patients, the use of morphine was associated with larger infarct size (mean troponin 1.14 ± 1.92 ng/mL vs. 0.83 ± 1.49 ng/mL, P = 0.01), longer hospital stay (6.5 ± 6.82 days vs. 4.89 ± 5.36 days, P = 0.004) and a trend towards increased mortality (5% vs. 2%, OR: 2.55, P = 0.06) in NSTE-ACS patients but morphine did not affect outcomes in the propensity matched STEMI patients. In a large retrospective study, morphine was associated with larger infarct size, a longer hospital stay and a trend towards increased mortality in invasively managed NSTE-ACS patients even after adjustment for clinical characteristics.